2020
DOI: 10.2147/ott.s248006
|View full text |Cite
|
Sign up to set email alerts
|

<p>STAT3-Induced Upregulation of lncRNA CASC9 Promotes the Progression of Bladder Cancer by Interacting with EZH2 and Affecting the Expression of PTEN</p>

Abstract: Long non-coding RNA (lncRNA) cancer susceptibility candidate 9 (CASC9) has been reported to play a vital role in tumorigenesis. This study explored the biological role of CASC9 and its regulation mechanism in bladder cancer (BC). Methods: Gene expression was evaluated using quantitative reverse transcription polymerase chain reaction and Western blot. The functional role of CASC9 in BC was studied using Cell Counting Kit-8, colony formation assay, scratch wound healing assay, transwell invasion assay, and xeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Similarly, lncRNAs can also regulate STAT3 expression and activation directly or indirectly through a variety of mechanisms, and this regulation is mostly achieved through endosomal competitive RNAs. For example, LINC00115 and CASC9 can further regulate STAT3 function by regulating downstream miRNA in cancer disease [ 39 , 40 ]. Moreover, activation of STAT3 can be induced by phosphorylation of some receptor tyrosine kinases themselves.…”
Section: Stat3 and Its Pathwaysmentioning
confidence: 99%
“…Similarly, lncRNAs can also regulate STAT3 expression and activation directly or indirectly through a variety of mechanisms, and this regulation is mostly achieved through endosomal competitive RNAs. For example, LINC00115 and CASC9 can further regulate STAT3 function by regulating downstream miRNA in cancer disease [ 39 , 40 ]. Moreover, activation of STAT3 can be induced by phosphorylation of some receptor tyrosine kinases themselves.…”
Section: Stat3 and Its Pathwaysmentioning
confidence: 99%
“…Virtually, CASC9 has been reported to interact with EZH2 and subsequently regulate gene expression at epigenetic levels. [28][29][30][31] RIP assay was used to evaluate the interaction between CASC9 and EZH2. We found that CASC9 was successfully pulled down by EZH2 compared with IgG control, indicating that CASC9 could bind to EZH2 directly (Figure 5(c)).…”
Section: Casc9 Epigenetically Mediates Pten Expression By Interacting...mentioning
confidence: 99%
“…IL-8 can reduce PTEN expression via phosphorylation to stimulate STAT3 signaling, resulting in enhanced cancer progression [ 161 ]. Furthermore, STAT3 can function as an upstream mediator of PTEN by activating lncRNA cancer susceptibility candidate 9 (CASC9) to diminish PTEN expression, resulting in bladder cancer progression [ 162 ]. On the other hand, miRNAs such as miRNA-551b-3p can induce STAT3 signaling in enhancing the growth and metastasis of cancer cells [ 163 ].…”
Section: Microrna and Pten Relationshipmentioning
confidence: 99%